From antimicrobial to anticancer: the pioneering works of Prof Luiz Rodolpho Travassos on bioactive peptides - Koskela Saara A; Figueiredo Carlos R (Springer, 2025)
Prof. Luiz Rodolpho Travassos, a distinguished Brazilian scientist, was instrumental in fostering an interdisciplinary research approach that seamlessly combined microbiology and oncology. This work has opened new pathways into the understanding of tumorigenesis and aided in the development of innovative therapeutic tools. One significant area of his work has been the exploration of bioactive peptides, many of which were first identified for their antimicrobial properties. These peptides demonstrate promise as potential cancer therapeutics due to their selectivity, cost-effectiveness, ease of synthesis, low antigenicity, and excellent tissue penetration. Prof. Travassos' pioneering work uncovered on the potential of peptides derived from microbiological sources, such as those obtained using phage display techniques. More importantly, in international cooperation, peptides derived from complementarity-determining regions (CDRs) that showed antimicrobial activity against Candida albicans further showed to be promising tools with cytotoxic properties against cancer cells. Similarly, peptides derived from natural sources, such as the gomesin peptide, not only had shown antimicrobial properties but could treat cutaneous melanoma in experimental models. These therapeutic tools allowed Prof. Travassos and his group to navigate the intricate landscape of factors and pathways that drive cancer development, including persistent proliferative signaling, evasion of tumor suppressor genes, inhibition of programmed cell death, and cellular immortality. This review examines the mechanisms of action of these peptides, aligning them with the universally recognized hallmarks of cancer, and evaluates their potential as drug candidates. It highlights the crucial need for more selective, microbiology-inspired anti-cancer strategies that spare healthy cells, a challenge that current therapies often struggle to address. By offering a comprehensive assessment of Prof. Travassos' innovative contributions and a detailed discussion on the increasing importance of microbiology-derived peptides, this review presents an informed and robust perspective on the possible future direction of cancer therapy.